1992
DOI: 10.1007/bf01709838
|View full text |Cite
|
Sign up to set email alerts
|

Fat emulsions containing medium chain triglycerides in patients with sepsis syndrome: Effects on pulmonary hemodynamics and gas exchange

Abstract: Fat emulsions containing medium chain triglycerides (MCT) have recently been introduced into clinical practice as a component of total parenteral nutrition. Since several authors reported increased pulmonary artery pressure and impaired gas exchange during intravenous (i.v.) fat use, in particular in septic patients, we studied the pulmonary hemodynamic and gas exchange effects of i.v. fat containing MCT and long chain triglycerides (LCT) in patients with sepsis syndrome. As the effects of fat emulsions have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
4

Year Published

1993
1993
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 25 publications
2
19
1
4
Order By: Relevance
“…There was no change in the shunt The lack of changes in pulmonary hemodynamics and gas exchange contrasts with data from other authors [37,38] who reported increased mean pulmonary artery pressure and a fall in arterial PO 2 due to increased mean venous admixture, in particular in patients with septic acute respiratory failure [38]. In these studies the infusion rate of the fat emulsion as well as the patients' baseline physiologic data were similar to those in the previous study [36]. The rise in plasma triglyceride levels, which in the past has been suggested to be responsible for the reported hemodynamic and gas exchange response [39,40], was comparable to the infusion of LCT at equivalent infusion rates as well.…”
Section: Pulmonary Hemodynamics and Gas Exchangecontrasting
confidence: 54%
See 2 more Smart Citations
“…There was no change in the shunt The lack of changes in pulmonary hemodynamics and gas exchange contrasts with data from other authors [37,38] who reported increased mean pulmonary artery pressure and a fall in arterial PO 2 due to increased mean venous admixture, in particular in patients with septic acute respiratory failure [38]. In these studies the infusion rate of the fat emulsion as well as the patients' baseline physiologic data were similar to those in the previous study [36]. The rise in plasma triglyceride levels, which in the past has been suggested to be responsible for the reported hemodynamic and gas exchange response [39,40], was comparable to the infusion of LCT at equivalent infusion rates as well.…”
Section: Pulmonary Hemodynamics and Gas Exchangecontrasting
confidence: 54%
“…Therefore, the different composition of the fat emulsion may explain the discrepancy between these studies and the previous one. In the study by Radermacher et al [36], although equivalent gram weights of lipids were administered, half of the triglycerides consisted of MCT which are oxidized faster than LCT [8,9] without acting as a precursor for prostaglandin formation. Not only altered prostaglandin synthesis but also a dose dependency as an underlying mechanism for different effects on pulmonary hemodynamics and gas exchange was recently discussed by Fiaccadori et al [41].…”
Section: Pulmonary Hemodynamics and Gas Exchangementioning
confidence: 99%
See 1 more Smart Citation
“…Lipid emulsion-induced pulmonary gas exchange disturbances can vary due to several factors, namely the different amounts of prostanoid precursors administered [4,8,10,13,14], the rate and duration of the lipid perfusion, and/or the pre-existing pathophysiological status of the lung [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…Radermacher et al [13], in patients with sepsis, and Fiaccadori et al [14], in patients following valvular heart surgery, did not observe changes in pulmonary haemodynamics nor in gas exchange abnormalities after the administration of an intravenous fat emulsion containing a physical mixture of medium-chain triglycerides and long-chain triglycerides (MCT/LCT: 50/50). MCT/LCT emulsions provide 26 % of linoleic acid and 4 % of alpha-linolenic acid, while those of LCT provide 55 % of linoleic acid and 7 % of alpha-linolenic acid.…”
Section: Introductionmentioning
confidence: 99%